The Effect of Welfare and Work Morale on Teacher Performance at Kharisma Vocational High School in Tangerang Regency - Dewi, Nurul Aulia; Sukarya, Yaya (UJoST- Universal Journal of Science and Technology, 2025)
The purpose of this study was to determine the influence of welfare and work morale on the performance of Kharisma Vocational School teachers, both partially and simultaneously. This quantitative study used the independent variables (X) of welfare and work morale, and the dependent variable (Y) of teacher performance. The sample consisted of 33 Kharisma Vocational School teachers, recruited through a questionnaire distributed on Google Forms. Data analysis was conducted quantitatively using SPSS. The results of the study revealed that the t-test showed that the welfare variable (X1) partially had a significant effect on teacher performance (Y), and the morale variable partially and significantly influenced teacher performance (Y). The f-test showed that the welfare and morale variables simultaneously influenced teacher performance. The effect of welfare and morale on teacher performance was 61.1%, while the remaining 38.9% was influenced by other variables not examined in this study.